ChemInform Abstract: Visible‐Light‐Induced Direct Photocatalytic Carboxylation of Indoles with CBr4/MeOH. Issue 17 (April 2016) - Yang, Qing‐Qing; Marchini, Marianna; Xiao, Wen‐Jing; Ceroni, Paola; Bandini, Marco
Abstract: A photoredox‐mediated carboxylation of heterocycles and even electron‐rich benzenes is described.